Incidencia de la música como estrategia didáctica en el proceso de enseñanza y aprendizaje al idioma inglés en los estudiantes del octavo año de la unidad educativa “Enrique Ponce Luque” sección vespertina, en el periodo lectivo 2016-2017 - Véliz Espinoza, Cristian Alberto (2016)
The English is one of the matters that at the moment are being demanded by his prolonged trajectory and importance as much in the economic thing by his dedicates and esteem that the developed countries have a greater affluence and they sell their products, but they come in his languages and this causes that we must have knowledge of the language. Like in the professional scope since such professional we must have certain degree of knowledge because at the present time more than all by young people who they learn of way different and one from them it is by means of music and they ask to us what means this, "we sang, but we do not know what we sang" and we remained with the question. Aside from having knowledge of general and global form; to be up-to-date with the newspaper to live on the people, by means of the social networks that are a small example: where we often found people who know another language and that we answered (nothing) Why she will be? The present project is based on the field of the education, for effect of the area of English is applied in the Educative Unit "Enrique Ponce Luque" located in the twon San Cristóbal of the Quevedo city. It is made the subject of "Incidence of music like didactic strategy in the process of education and learning to the English language in the students of the eighth year of the Educative Unit" Enrique Ponce Luque "vespertine section, in lectivo period 2016-2017". Addressing to look for a new strategy to us to apply within the educative area (hour class) with the students and to take advantage of it. Proposing with such students a class with music the one that they like more and to establish the class with music.